Ekstraksi Dan Karakterisasi Kitosan Dari Kulit Udang Windu (Penaeus monodon) Serta Proses Depolimerisasi Kitosan Dengan Hidrogen Peroksida Berdasarkan Variasi Suhu Pemanasan - Tanasale, Matheis F.J.D.P.; Telussa, Ivonne; Sekewael, Serly J. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2016)
An extraction of chitin from shell of the tiger shrimp (Penaeus monodon), a convertion chitin into chitosan and depolymerization chitosan into oligochitosan using hydrogen peroxide based on variations in heating temperature have been done. Chitosan had depolymerized and it’s molecular weight had tested by end group analysis method and it’s degree of deacetylation had tested by UV-Vis spectrophotometry method. Oligochitosan had obtained from the conversion of chitin is isolated from the shell of tiger shrimp and from commercial chitin. The content of chitin obtained in tiger shrimp shells was 35.90% while the result of the conversion of commercial chitin into chitosan amounted to 62.33%. Characterization of functional groups using FTIR spectrophotometry showed that the conversion of chitosan from chitin commercial have absorption bands of 3617.56 (OH), 3050.47 - 3127.63 (-NH stretching), 2894.24 (-CH methylene), 1679.06 (-C = O), 1564.30 (-NH bending), and 1076.30 cm-1 (-CO-). The commercial chitosan which is characterized by FTIR spectrophotometric method also supports the results of the conversion of chitosan from chitin commercial. In the process of depolymerization of chitosan by hydrogen peroxide was found that the greater heating temperature was used, the smaller the percent yield and molecular weight of oligochitosan were at 40 oC, 50 oC, 60 oC and 70 oC gained weight average molecular oligochitosan were 1030.12 g/mol, 1019, 28 g/mol, 978.12 g/mol, and 908.82 g/mol, respectively